IMPLEMENTASI PROGRAM ASSISTENSI REHABILITASI SOSIAL DALAM PEMENUHAN HAK ANAK YATIM, PIATU DAN YATIM-PIATU DI KECAMATAN MERIGI SAKTI KABUPATEN BENGKULU TENGAH - Elda Eka Sari; Sri Putri Permata; Alfarabi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the implementation of the Social Rehabilitation Assistance Program (ATENSI) by the Ministry of Social Affairs in fulfilling the rights of orphaned children in Merigi Sakti District, Central Bengkulu Regency. The background of this study highlights the high number of orphaned children who require state protection through targeted social programs. This research aims to analyze how the Social Rehabilitation Assistance Program is implemented in fulfilling children's rights to survival, development, protection, and participation. The theoretical framework focuses on policy implementation concepts, including stages of socialization, implementation, monitoring, evaluation, and the legal basis of Minister of Social Affairs Regulation Number 7 of 2021. The method used is a descriptive qualitative approach through interviews, observations, and documentation involving informants from program implementers, local government, and beneficiaries. The results show that the program implementation has been carried out through socialization processes, data verification, distribution of assistance, and periodic monitoring. The program provides tangible benefits in meeting educational, health, and basic needs of the beneficiary children. However, the study also identifies limitations in data validation, target distribution, and coordination among implementers. Overall, the Social Rehabilitation Assistance Program serves as an important instrument in the social protection of orphaned children, but it requires improvements in planning, evaluation, and expansion of coverage to ensure more optimal and equitable fulfillment of children's rights.